Answer:
y =
![(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/54kd5otoayi7fslqp2ejx77tdkhh8ubevy.png)
Explanation:
Given that y varies inversely with x then the equation relating them is
y =
← k is the constant of variation
To find k use the condition y =
when x =
, thus
=
= 2k ( divide both sides by 2 )
k =
![(1)/(6)](https://img.qammunity.org/2021/formulas/mathematics/college/qvdnhfynctmwjvm1ll5tom8i638hmdyvry.png)
y =
← equation of variation
When x =
, then
y =
=
=
![(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/54kd5otoayi7fslqp2ejx77tdkhh8ubevy.png)